Analisis Sifat Mekanik Material Komposit Ecenggondok Berbahan Filler Ampas Singkong Dengan Matrik Polyester - Karyanik Karyanik; Nasmi Herlina Sari (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2016)
The using of composits material currently more developed together with the using of it from the simpler like larges of housing tools to industry sector.The composite resech supported by fiber of eichhornia crassipes solms that has filler of cassava waste that has functions to know tensile strength and impact strength.This reseach used the various added of cassava waste , 0, 20, 25, and 30 (% of weight) and using of polyester resin matrix, the form of the composite speciment is plat with the fractions volume eichhornia crassipes solms fiber 20 % (constant), the fiber length 25 mm, because methode to found eichhornia crassipes solms fiber using methode of manual so that nothing of fibers have cuality and length with the same.Composite manufacturing process carried out by the methode of hand lay up with emphasis manually using glass as a mold and pressure.The results tensile reseach founded that lests of filler as used so that the higest that tensile strength, the highest tensile strength at variations added of cassava waste 0 % ( 9,311 N/mm2 ) and for impact strength the biggest added of cassava waste so that the highest energy to fight of materials , the high tensile strength found in the variations added of cassava waste 25 % ( 0,018282 J/mm2 ).The using of composits material currently more developed together with the using of it from the simpler like larges of housing tools to industry sector.The composite resech supported by fiber of eichhornia crassipes solms that has filler of cassava waste that has functions to know tensile strength and impact strength.This reseach used the various added of cassava waste , 0, 20, 25, and 30 (% of weight) and using of polyester resin matrix, the form of the composite speciment is plat with the fractions volume eichhornia crassipes solms fiber 20 % (constant), the fiber length 25 mm, because methode to found eichhornia crassipes solms fiber using methode of manual so that nothing of fibers have cuality and length with the same.Composite manufacturing process carried out by the methode of hand lay up with emphasis manually using glass as a mold and pressure.The results tensile reseach founded that lests of filler as used so that the higest that tensile strength, the highest tensile strength at variations added of cassava waste 0 % ( 9,311 N/mm2 ) and for impact strength the biggest added of cassava waste so that the highest energy to fight of materials , the high tensile strength found in the variations added of cassava waste 25 % ( 0,018282 J/mm2 ).